PENGARUH KONSUMSI OMEGA-3 TERHADAP GEJALA DEPRESI PADA ORANG DEWASA SEBUAH SYSTEMATIC REVIEW - Risa Ika Meidiana (2021)
Introduction: depression is mood disorder that causes the leack of interest and happiness. In an episode of depressive disorder, there are several symptoms, one of which is a reduced of appetite. With those transformation of someone behaviour are able to causes the changes of appetite. One of the nutrition that is lacking because of appetite is omega-3 fatty acids. Omega-3 have a biologic role as a part of membrane phospholipids and as signaling molecules that have important role functionally in brain. The variant in acid membrane composition effect the protein function that attach membrane, such as transporter, ion channel, and receptor. For the patient with depression disorder, the composition of serum fatty acid, plasma, erythrocytes, or adipose tissue are have the lowest level. Method: Systematic Review by conducting literature searches using the PubMed and Mendeley databases. Literature that discusses omega-3 and depression. Result: there are 4 studies that describe the effect of omega-3 on depression, with the results that 3 out of 4 journals, there are significant differences between the groups given omega-3 and placebo. Conclusion: there is an effect by giving omega-3 towards depressive symptoms.